Apartemen Di Pekanbaru Dengan Pendekatan Arsitektur Hijau - Yogi Efrinaldi; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru City which is now a metropolis with a population of more than one million also will require a wide range of facilities that can support the ease and comfort and security for residents and visitors who come to town there and this, that's the reason for the construction of residential vertically. In the design of the apartment, design approach emphasizes the aspects of green architecture with the goal of keeping buildings designed to minimize the adverse effects of the energy crisis, the adverse effects on the environment, natural, or user of the apartment itself. However, to support this design is more in the concept captured the "movement", the concept is applied to the movement in the form of building and landscape. The principles of green architecture that is implemented into an apartment building in accordance with the principle of Brenda and Robert Valle namely, (1) Save Energy, (2) Taking into account the climatic conditions (3), Maximizing renewable natural resources, (4) Not a bad impact on the environment , (5) in response to the state of the treadKeywords: Apartment, movement, principles of green architecture according to Brenda and Robert Valle